Experimental investigation of feedforward control schemes of a flexible robot manipulator system - Ahmad, M. A.; Mohamed, Z.; Ismail, Z. H. (Faculty of Electrical Engineering, 2008)
This paper presents experimental investigations into the applications of feedforward control schemes for vibration control of a flexible manipulator system. Feedforward control schemes based on input shaping and filtering techniques are to be examined. A constrained planar single-link flexible manipulator is considered in this experimental work. An unshaped bang-bang torque input is used to determine the characteristic parameters of the system for design and evaluation of the input shaping control techniques. The input shapers and filtering techniques are designed based on the properties of the system. Simulation results of the response of the manipulator to the shaped and filtered inputs are presented in time and frequency domains. Performances of the shapers are examined in terms of level of vibration reduction and time response specifications. The effects of derivative order of the input shaper on the performance of the system are investigated. Finally, a comparative assessment of the control strategies is presented and discussed